TRADISI PENGHORMATAN DEWA DALAM MASYARAKAT TIONGHOA BEKASI - Hartati, C. Dewi (Bambuti, 2020)
This article discusses the practice of the cult of templeâ€s deity. This cult is said to be a reinvented tradition. The tradition is created because it is formed by the elements that come from the original tradition. By tracing the process of discovering the Hobsbawm tradition from the sacred and profane aspects of Durkheim and its relation to totemism, it is evident that this tradition has a new form and function. The original function of tradition was to strengthen identity, but the new function of the reinvented tradition appears to be an integrative function. The reinvented tradition also occurs in an effort to attract public interest or attention to make it more popular in the community. The temple community carries out an invented traditional process so that the tradition of the cult becomes more attractive, and is preferred more popular, through the appearance of entertainment shows at festivals.